The Effectiveness of PBL Models Based on Google Meet on the Ability of Mathematical Problem Solving - Danis Safitri; Nurafni Nurafni (Jurnal Ilmiah Sekolah Dasar, 2021)
Pandemic Covid-19 has a big influence on various sectors, including the education sector. This makes educators make an innovation in the learning model, which combines a model of PBL-based google meet. The purpose of this study is to analyze the presence or absence of the influence of the PBL models based on google meets on the ability of mathematical problem-solving in grade IV during distance learning. The type of research used by researchers, namely quantitative. With research design a quasi-experiment with posttest only group design. Subjects in this study were students of class IV as many as 64 students. Data collection techniques interviews and tests. While the research instrument is in the form of a posttest. Data analysis used is descriptive analysis, a test of homogeneity, normality test, hypothesis test (t-test), and test the effect size. The results showed that the average value of the posttest experimental class of 76,25 higher than the control class that is 62,18. In hypothesis testing via t-test obtained the value of sig 0.47 that where the value is smaller than Î±=0.05 so that H0 is rejected and H1 is accepted. This means that there is an influence of the use of PBL models based on google meet on the ability of mathematical problem-solving in grade IV. So, the use of PBL models based on google meet can be applied to learning online.